mportance of social networks in bioethics - Domenack-Bracamonte, Augusto (2023)
Objective: To analyze if social networks distort learning about when does human life begin? Since when has a human being been a person? And when does human dignity appear? in third cycle students of health sciences from a private university in Lima. Methodology: Observational, quantitative, descriptive and cross-sectional study where the population studied were undergraduate health sciences university students from a private university in Lima. Participation was anonymous and voluntary and the inclusion criteria were: being a student, being of legal age and study third academic cycle. Results: The results showed that the incorrect use of social networks contributes to the distortion of Ethical and/or Bioethical knowledge in relation to the Beginning of Life, Person and Human Dignity. Conclusions: Social networks such as Facebook, Instagram, YouTube, WhatsApp and TikTok distort the learning of university students and this translates into a low level of knowledge of ethical and bioethical issues about the beginning of human life, when is a person the being human and when human dignity appears.